Study of the lipid and inflammatory profile in diabetic individuals: Literature review (Research, Society and Development, 2025)
Lipid profile assessment plays a crucial role in the management of diabetes mellitus, particularly in patients with type 2 diabetes (T2D), where dyslipidemia is prevalent. This assessment typically includes measurements of total cholesterol, low-density lipoprotein (LDL), high-density lipoprotein (HDL), and triglycerides, which collectively provide information on cardiovascular risk. These lipid abnormalities significantly contribute to the development of atherosclerosis and cardiovascular disease, which are the leading causes of morbidity and mortality in diabetic populations. Therefore, regular lipid profile assessments allow physicians to identify high-risk patients early, facilitating targeted interventions, such as lifestyle modifications and lipid-lowering therapies, to mitigate cardiovascular risks. This research aims to conduct a literature review on the lipid and inflammatory profile in diabetic patients. To achieve this objective, a bibliographic search was conducted in databases such as the Virtual Health Library (VHL) and articles, dissertations, and theses available in the indexes SCIELO (Scientific Electronic Library Online), LILACS (Latin American Literature in Health Sciences), and MEDLINE (Ministry of Health Virtual Health Library). After applying the established inclusion and exclusion criteria, eight articles that met the requirements for the literature review were selected. The results demonstrate a notable correlation between lipid abnormalities and systemic inflammation in individuals with diabetes, further emphasizing the complex interplay between these factors. Patients with dyslipidemia often have elevated inflammatory markers, suggesting that lipid disorders may trigger or sustain inflammatory processes.